Parallel computational fluid dynamics multidisciplinary applications : proceedings of the Parallel CFD 2004 Conference, Las Palmas de Gran Canaria, Spain (May 24-27, 2004) - Parallel CFD 2004 Conference (2004 : Las Palmas, Canary Islands); Winter, G. (Gabriel) (Amsterdam ; Oxford : Elsevier, 2005)
Parallel CFD 2004, the sixteenth international conference on Parallel Computational Fluid Dynamics and other modern scientific domains, has been held since May 24th till May 27th, 2004 in Las Palmas de Gran Canaria, Spain. The specialized, high-level Parallel CFD conferences are organised on travelling locations all over the world, yearly because of multidisciplinary subject of parallel CFD and its rapidly evolving nature. The conference featured 8 invited lectures, 3 Mini Symposia, contributed papers and one Tutorial & Short Course. More than 80 multi-disciplinary presentations of the Parallel CFD had been presented, with participants from 17 countries. The sessions involved contributed papers on many diverse subjects including turbulence, complex flows, unstructured and adaptive grids, industrial applications, developments in software tools and environments as parallel optimization tools. This Book presents an up-to-date overview of the state of the art in parallel computational fluid dynamics. - Report on current research in the field. - Researchers around the world are included. - Subject is important to all interested in solving large fluid dynamics problems. - It is of interest to researchers in computer science, engineering and physical sciences. - It is an interdisciplinary activity. Contributions include scientists with a variety of backgrounds. - It is an area which is rapidly changing.
Part 1: Direct Numerical Simulation & Large Eddy Simulation (I) -- Part 2: Spectral Element Method & Lattice Boltzman Methods -- Part 3: Grid Computing & Integred Platform & Montecarlo Simulation -- Part 4: Energy Physics -- Part 5: Direct Numerical Simulation & Large Eddy Simulation (II) -- Part 6: Aerodynamic Flow -- Part 7: Mesh Strategies -- Part 8: Environmental Flows & Ecology Problems -- Part 9: Radiation -- Part 10: Kelvin-Helmhotz Instability -- Part 11: Complex Flows -- Part 12: Unsteady Flow Computation & Efficiency Issues -- Part 13: Flow Control & Flow Codes -- Part 14: Metacomputing & Time Integration -- Part 15: Multigrid & Load Balancing & Security in Distributed Parallel Computation.
Revised conference papers.
Includes bibliographical references.
Keywords: Fluid dynamics -- Data processing -- Congresses; Parallel processing (Electronic computers) -- Congresses; Supercomputers -- Congresses; Electronic books